Evaluasi Penggunaan Fixed Phone di Lingkungan Polri dalam Rangka Mendukung Pelaksanaan Tugas Kepolisian yang Efektif dan Efisien: Evaluasi Penggunaan Fixed Phone di Lingkungan Polri dalam Rangka Mendukung Pelaksanaan Tugas Kepolisian yang Efektif dan Efisien - Raslin, Harvin; Astuti, Septi; Sakapurnama, Eko; Suryadi, Suryadi; Wahyono, Ary (Jurnal Litbang Polri, 2025)
A fixed phone is a telecommunications device connected by cable to a fixed location, such as a home or office, with a permanent phone number. Although often considered outdated compared to mobile phones, fixed phones remain crucial in sectors requiring security and confidentiality, such as the Indonesian National Police (Polri). Within Polri, fixed phones are used for both internal and external communication to support police duties. This study aims to analyze the use and quality of fixed phones and assess the management of their deployment as an effective and efficient communication tool for police tasks. The research employs both qualitative and quantitative methods, including interviews, observations, questionnaires, and checklists. The findings indicate that the use of fixed phones is declining due to technological advancements like mobile phones and handie-talkies (HT). Fixed phones within Polri are categorized into three conditions: active for calls, active but not used (bundled with IndiHome), and inactive but still registered. While the quality of active fixed phones is good, there are issues with a lack of understanding regarding their function. Management issues include the absence of standard operating procedures (SOP), inadequate service mechanisms, and budget inefficiencies. Therefore, there is a need to remove unused numbers, ensure active connections at the Police Command and Control Center (SPKT), update service number information, optimize the use of PABX/IP-PBX systems, develop SOP and supervision mechanisms, coordinate with providers for cost standardization, migrate to VoIP, and raise awareness about the importance of fixed phones.